Analysis of Passenger Service Satisfaction of Public Transport in Tangerang City - Oktavia, Santi; Dwiatmoko, Hermanto (ASTONJADRO, 2022)
With the presence of public transport "Si Benteng,” we hope that it could fulfill the needs of public transport in Tangerang City, and also decrease the traffic in the city. The purpose of this research is to know the quality of public transport "Si Benteng” in Tangerang City and an effort to increase the quality and passenger satisfaction of public transport "Si Benteng”. The respondent of this research is the people of Tangerang City with an average age of 17 to 60 years old with a total of 215 respondents by conducting a direct survey, by distributing questionnaires to public transport users of "Si Benteng”. The method of this research is Structural Equation Modeling (SEM). From the results obtained, the most dominant public transport user of "Si Benteng” is women with an average age of 17-35 years old and 35-55 years old of the users has at least finished high school, and their occupation of them mostly consist of a general employee with an income and outcome of > Rp 3.000.000,- a month. At the same time, the direct influence of service quality on passenger satisfaction is 0.867, and passenger satisfaction on passenger loyalty is 1.283. It can be concluded that passenger satisfaction has the greatest influence on passenger loyalty. The quality of service that needs to be improved is that passengers do not have to wait long for the arrival of "Si Benteng” public transportation, Availability of shelter facilities, and the distance to the shelter is too far. The conclusion of this research is the result of the hypothesis that service quality has a positive and significant to passenger satisfaction and passenger satisfaction has a positive and significant to passenger loyalty